Bibliometric Analysis of Development Map And The Direction of Religious Moderation Research In Scopus Database 1988-2024) - Khalil, Mohammed Thoha; Al Manfaluthi, Lutfi Zaki; Al Mubarok, Fahmi Ulum; Saiffudin, Moh. (Universitas Muhammadiyah Surakarta, 2024)
This study aims to conduct a bibliometric analysis of the development and direction of religious moderation research registered in the Scopus database from 1988 to 2024. The analysis method in this study is carried out in three stages, first conducting a literature review of related themes to ensure that relevant research is carried out on bibliometric topics; second, conduct a search to get an idea of whether the research will cover a number of minimum required ; third, do analysis document end search with using Scopus analyzer and R and Rstudio to find out the number of documents per year, document based on journal, writer, affiliate, country And subject/field. Next is done analysis to level Network document with read visualization through VOSviewer and Microsoft Excel data processing with co-authorship analysis type ( co-authorship ), say key ( co-occurrence ) , And partner bibliometrics ( bibliometric coupling ). The results of the analysis show that there has been a significant increase in the number of publications related to religious moderation, especially after 2010, reflecting the increasing academic attention to this issue. This study also identified several key themes, such as religious moderation education, the role of government in promoting moderation, and the challenges faced in implementing moderation values in society. The findings in this analysis are expected to provide a broader understanding of scientific insight for researchers and policy makers in formulating strategies to implement religious moderation programs, especially in Indonesia, which has the largest Muslim population in the world.